PRIMERS: Polydopamine Radioimmunotherapy with Image-Guided Monitoring and Enhanced Release System - Shahinur Acter; Lindokuhle M. Ngema; Michele Moreau; Debarghya China; Akila Viswanathan; Kai Ding; Yahya E. Choonara; Sayeda Yasmin-Karim; Wilfred Ngwa (MDPI AG, 2024)
Background/Objectives: To overcome the side effects of conventional cancer treatment, multifunctional nanoparticles with image-guidance properties are increasingly desired to obtain enhanced therapeutic efficacy without any toxicity of the treatment. Herein, we introduce the potential of Polydopamine Radioimmunotherapy with Image-guided Monitoring and Enhanced (drug) Release System (PRIMERS) to meet the challenges of currently used cancer therapy. Methods: The PDA nanobowls were synthesized using an emulsion-induced interfacial anisotropic assembly method followed by surface modification with high-Z material to obtained the final product PRIMERS. Results: The engineered multifunctional nanosystem "PRIMERS" could serve as fiducial markers with the potential for use in combination cancer therapy. By leveraging the advantages of the excellent surface functionalization capability of PDA, the anisotropic nanostructure (PDA nanobowls) has been successfully functionalized with gadolinium, which shows strong MRI contrast signal both in vitro in phantom and in vivo in animals. The results of anti-cancer drug loading and releasing efficiency of these functionalized nanobowls are presented. Moreover, the gadolinium-coated PDA nanobowls demonstrate the capacity for loading immunotherapy drugs (Anti-CD40) with activated release in acidic pH levels characteristic of the tumor microenvironment, with enhanced release following administration of radiation therapy in vitro. Conclusions: Overall, the results highlight the potential of this new technology for combining radiotherapy with activated image-guided drug delivery, which offers broad opportunities to overcome current challenges in cancer treatment.